HeartMate 3 upgrade and aortic root replacement for severe aortic insufficiency and ventricular fibrillation - Katlin T. Schmitz, MD; Sara S. Inglis, MB, BCh, BAO; Mauricio A. Villavicencio, MD, MBA; Adrian daSilva-deAbreu, MD, MSc, PhD(c) (JHLT Open)
A 31-year-old woman with left ventricular (LV) assist device (LVAD) support presented with refractory ventricular arrhythmias attributed to severe aortic insufficiency and inadequate left ventricular offloading. The patient had a history of 2 prior pump exchanges in the setting of chronic polymicrobial driveline infections and prior transcatheter aortic valve implantation (TAVI). She underwent aortic valve replacement for management of her ventricular arrythmias. Due to her complicated surgical history, right heart failure, and prolonged cardiopulmonary bypass time the surgical aortic valve replacement and HeartMate 3 upgrade was complicated, but surgery was successful with subsequent termination of her ventricular arrythmias.